The Mediating Role of Avoidant Personality Disorder Features in the Relationship Between Stressful Life Events and Depression Among First-Year University Students - Zhou H; Niu S; Guo Y; Qin Y; Sun H; Mu F; Duan X; Zheng Y; Zhang Y; Liu Y; Liu N (Psychology Research and Behavior Management)
Huihui Zhou,1,* Sifang Niu,1,2,* Yangziye Guo,1,3 Yan Qin,1,3 Hao Sun,4 Fuqin Mu,5 Ximing Duan,5 Yi Zheng,5 Ying Zhang,6 Yan Liu,1 Ning Liu7 1School of Public Health, Jining Medical University, Jining, 270213, People’s Republic of China; 2School of Public Health and Management, Binzhou Medical University, Yantai, 264003, People’s Republic of China; 3School of Public Health, Shandong First Medical University, Jinan, 250117, People’s Republic of China; 4School of Clinical Medicine, Jining Medical University, Jining, 270213, People’s Republic of China; 5School of Mental Health, Jining Medical University, Jining, 272013, People’s Republic of China; 6School of Public Health, University of Sydney, Sydney, NSW, 2006, Australia; 7School of Basic Medicine, Jining Medical University, Jining, 272067, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Liu, School of Public Health, Jining Medical University, Jining, 272065, People’s Republic of China, Email hakunaly@163.com Ning Liu, Department of Graduate, Jining Medical University, Jining, 272065, People’s Republic of China, Email 631864@qq.comPurpose: Stressful life events are risk factors of depression. To explore whether the avoidant personality disorder (AVPD) features play a mediating role between stressful life events (SLEs) and depression among Chinese first-year university students.Methods: The cross-sectional study was conducted from April to October 2018. The participants were the freshmen selected from Jining Medical University and Weifang Medical University (n=7390) in Shandong Province in China. Depression was assessed by the Beck Depression Inventory-II, AVPD were measured by the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM 5). The data were processed and analyzed by SPSS24.0 software, Pearson correlation analysis and PROCESS3.3 program intermediary analysis. The method of Bootstrap was adopted to determine whether the AVPD features act as mediating factors in the association between the NLEs and depression.Results: A total of 34.68% of the participants reported one to three AVPD features, and 18.15% reported four to seven AVPD features. AVPD features (r=0.384, P< 0.05) and the SLEs (r=0.309, P< 0.05) were positively related to the risk of depression, respectively. AVPD features play a partial mediating effect on the relationship between SLEs and depression (the effect value is 0.133, P < 0.01; 32.28% of the total effect).Limitation: There might be recall bias in this cross-sectional study.Conclusion: AVPD features are prevalent among Chinese university students. AVPD features displayed the mediation effect on depression related to stressful life events. Psychological interventions for depression in college students should focus not only on stress but on individual personality traits and cognitive mode. Care-givers, teachers, and health professionals should pay more attention to the early identification of the AVPD features among university students.Keywords: stressful life events, depression, avoidant personality disorder, mediator